(untitled) (Bangladesh Journal of Botany, 2008)
Centaurea L. sect. Ptosimopappa, a local endemic group in the Mediterranean and South East Anatolia, is represented by only two species, namely C. ptosimopappa Hayek and C. ptosimopappoides Wagenitz in Turkey. Both these species show a very restricted distribution as serpentine habitat indicators and are recorded as vulnerable. Present study was carried out to enlighten the morphological, anatomical and ecological features of these two species in detail. The structure of achene, indumentum and pollen grains were investigated by using Scanning Electron Microscope (SEM). The capitulum, involucre and leaf structure of these two species are rather similar, but their achenes and pollen grains differ from each other. In C. ptosimopappa pollen spinules are densely distributed but in C. ptosimopappoides they are sparsely distributed. The achenes are obovate in C. ptosimopappa and rectangular in C. ptosimopappoides. C. ptosimopappa is a scrub species but C. ptosimopappoides is a subscrub species. A negative relation in terms of the proportion of sand to silt content of the soil and positive relation between the percentage of CaCO3 and pH was observed for C. ptosimopappa (p < 0.05). A negative relation in terms of the proportion of sand to silt content of the soil was observed in C. ptosimopappoides (p < 0.01). Â Key words: Morphology, Anatomy, Ecology, Pollen, Centaurea spp. doi:10.3329/bjb.v37i1.1566 Bangladesh J. Bot. 37(1): 67-74, 2008 (June)